SARS and human rights in a postmodern context : a case study of Toronto - Snellman, Pauliina (2008)
This pro gradu-thesis studies the conflict between human rights and Severe Acute Respiratory Syndrome (SARS). The thesis focuses on the events that took place in Toronto between February and June 2003. The theoretical focus is placed within postmodern tradition and the main contributors for the theoretical approach in this work are Michel Foucault and Georgio Agamben. Especially the concept of biopolitics and politics of the state of exception are closely analysed. The key aspect of this thesis is in the temporality of human rights and the events that lead to revoking those rights. A great emphasis is placed on describing the interdependence between human rights and citizenship. In addition to human rights debate the aim is to explore the relationship between disease and war and to study how this relationship changed during SARS epidemic. I argue that SARS epidemic marked a new era in global governance; for the first time universal threat challenged the traditional alert and response mechanisms. The question that remains is did SARS, the invisible enemy, create a constant state of exception that invalidates human rights whenever there is a biological threat.